Congenital diaphragmatic hernia in Northern Queensland. Issue 6 (3rd June 2013) - Edmonds, Liza; Boniface, Cherie; Alcock, Gary; Stalewski, Harry; Shi, Edward
<x xml:space="preserve">Abstract</x> Aims To investigate the survival of non‐syndromic live born infants diagnosed in Northern Queensland with congenital diaphragmatic hernia (CDH). Method Case note audit was completed of all live born newborns with a diagnosis of CDH admitted between February 1987 and December 2010. Demographic and clinical data were extracted. Results Overall survival to time of discharge for all infants was 67.3% (n = 35/52). For infants born before 2003 survival was 59.5% and for those born in 2003 and onwards was 86.7% (P = 0.10, OR 4.4, 95% confidence interval (CI) 0.87–22.55). Infants born prior to 2003, compared to those born from 2003 onwards, were less likely to survive with an isolated defect (P = 0.04, OR 8.0, 95% CI 0.93–68.62). Isolated congenital diaphragmatic hernia survival since 2003 was 92.3%. A significant difference was found in the time to surgery with those born in 2003 onwards having surgery significantly later, median 134 h, compared to the earlier cohorts median time to surgery of 83 h (P < 0.005, 95% CI 32.61–167.09). Premature infants had poorer survival (46.7%) compared to term infants (75.7%) (P < 0.0001 OR 3.6, 95% CI 1.99–6.68). Univariate analysis identified low birthweight was associated with poorer survival. Conclusions Survival to discharge in our cohort equals other reported rates in Australia and around the world, including centres with tertiary paediatric services. The current management strategies used for these infants have seen a significant improvement in outcomes over time.